Antecedents and Consequences of Impulse Buying Consumer on Tiktok Shop - Aghnia Salma Salsabila; Adi Santoso; Wahna Widhianingrum (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine consumers' impulsive purchases at Tiktok Shop based on antecedents and consequences explained by the variables of impulsive behavior, online consumer reviews, purchase decisions and loyalty. This study uses a quantitative approach with data analysis methods, namely product moment correlation. The sample determined in the study used purposive sampling and obtained as many as 302 respondents who had made purchases at the Tiktok Shop. The results of the study show that Consumer Impulsivity has an influence on Impulsive Buying, meaning that consumers who have high impulsive reactions will usually buy products impulsively.